The people left out of Treaty 8 - Smillie, Christine Mary (2005)
The story of how and why the Canadian government negotiated Treaty 8 with First Nations living in north-western Canada, and its attitude toward the people whom it casually left out of treaty, provide an excellent example of how the Canadian government approached treaty negotiations in the late nineteenth and early twentieth centuries. Treaty 8 is both typical of the other numbered treaties negotiated with First Nations in the late nineteenth century in western Canada as well as different, in that it was the first of the "northern" numbered treaties negotiated with First Nations. This thesis looks at Treaty 8 in both ways: how it illustrates a common approach to treaty making on the part of the Canadian government, and how it differs from other treaties and other treaty negotiation processes. The thesis also tells the story of the people left out of Treaty 8 negotiations in northern Alberta and north-western Saskatchewan, as well as their struggles to obtain justice for this governmental oversight. This thesis looks at a number of issues related to Treaty 8 which earlier historians have either not focused on or overlooked. The first is that the territory covered by Treaty 8 is greater than the area into which treaty commissioners were sent in 1899 and 1900. The second related point is that the government policy of the time that treaties should be negotiated at as little expense and cost to the government as possible meant that people were left out of treaty negotiations.